1999
DOI: 10.3109/01674829909075574
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women benefit from massage therapy

Abstract: Twenty-six pregnant women were assigned to a massage therapy or a relaxation therapy group for 5 weeks. The therapies consisted of 20-min sessions twice a week. Both groups reported feeling less anxious after the first session and less leg pain after the first and last session. Only the massage therapy group, however, reported reduced anxiety, improved mood, better sleep and less back pain by the last day of the study. In addition, urinary stress hormone levels (norepinephrine) decreased for the massage therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
116
2
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(126 citation statements)
references
References 25 publications
4
116
2
3
Order By: Relevance
“…Shim et al [9] recommended good posture and regular exercise as a method of reducing LBP. Massage therapy has been shown to be effective for reducing LBP and decreasing levels of anxiety [10]. Carr [11] indicated that the use of orthotheses such as sacroiliac belts can significantly reduce pain and lessen the effects on daily life; however, Vleeming et al [13] identified no evidence for the use of a pelvic belt as a stand-alone treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Shim et al [9] recommended good posture and regular exercise as a method of reducing LBP. Massage therapy has been shown to be effective for reducing LBP and decreasing levels of anxiety [10]. Carr [11] indicated that the use of orthotheses such as sacroiliac belts can significantly reduce pain and lessen the effects on daily life; however, Vleeming et al [13] identified no evidence for the use of a pelvic belt as a stand-alone treatment.…”
Section: Introductionmentioning
confidence: 99%
“…14,19,23,28,39 Thirteen studies did not specifically focus on lumbopelvic pain and included pregnant women. 6,[10][11][12][13]17,21,22,26,29,32,38,40 Outcome Measures The effectiveness of treatment was measured by a variety of outcome measures, but most studies used pain or disability. For pain, the visual analog scale 19,22,24,28,31,39,40 and numeric pain rating scale 5,6,14,23,26,35 were the most commonly used measurement tools.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Field et al, in their three studies (1999, 2004, and 2009), reported that relaxation instruction and massage therapy can decrease the incidence of pregnancy. 3,11,12 Brown et al also reported that yoga can decrease pregnancy depression by decreasing the maternal cortisol level. 13 Attachment is a close and permanent relationship between mother and her baby that facilitates the mother-baby interaction and creates a close bilateral emotional relationship just after delivery.…”
Section: Introductionmentioning
confidence: 99%